2009
DOI: 10.1007/s11255-009-9578-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prostate cancer incidentally detected in radical cystoprostatectomy specimens from Japanese men with bladder cancer

Abstract: Clinicopathological features of incidentally detected prostate cancer are markedly more favorable than those of clinically detected prostate cancer, which may reflect less aggressive biological phenotypes of incidental prostate cancer arising in Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
10
1
1
Order By: Relevance
“…However, the incidence rate was much lower in most of the Asian countries. According to the recent studies with 1207 cases from Asia, the prevalence of incidental prostate cancer was only about 10.9% [13], [19]–[25]. It was extremely low in China, Japan and India.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence rate was much lower in most of the Asian countries. According to the recent studies with 1207 cases from Asia, the prevalence of incidental prostate cancer was only about 10.9% [13], [19]–[25]. It was extremely low in China, Japan and India.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [22] shows that just for 4% of all 248 studied patients incidentally found prostate cancer was found in Taiwan. A bit more cases of incidentally found cancer were found in the Kurahashi et al [23] study. Incidentally found cancer after RCP was diagnosed for 33.3% of all examined patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of incidental PCa varied among countries and cohorts, even though all the studies were carried out in similar periods, ranging from 1988 to 2008. Among all the studies carried out, the prevalence was consistently high in Japan and Korea (12.3% and 26.1%, and 51.7% and 50.0%, respectively). In the studies on incidental PCa, tumor grade was evaluated using the Gleason score.…”
Section: Prevalence Of Latent and Incidental Prostate Cancer In Asianmentioning
confidence: 94%
“…Table summarizes the results of studies on latent and incidental PCa in Asian men. Pathological examinations were carried out using 3–5‐mm step sections in all the studies, with the exception of a study on incidental cancer from Iran . The majority of the latent cancer studies reported on Japanese men, except for two studies from Singapore and Iran.…”
Section: Prevalence Of Latent and Incidental Prostate Cancer In Asianmentioning
confidence: 99%
See 1 more Smart Citation